Social contract: Evolution of ideas and lessons of history - A. N. Danilov (RUDN journal of Sociology)
The article is a review of the book by Zh.T. Toshchenko Fates of Social Contract in Russia: Evolution of Ideas and Lessons of Realization (Moscow; 2025. 844 p.). The book describes the emergence of the ideas of social contract as an agreement between the people and the state, often of a latent nature, which were first developed by thinkers of Enlightenment. The author considers various theories of social contract, revealing peculiarities in its contemporary interpretation and fulfillment and focusing on the main characteristics of social contract, its essence as a unity of goals of all participants striving for mutual trust, balance of interests and constant feedback. The author provides a review of the contemporary interpretations of social contract and of the new options for understanding practices of its implementation in the social-political life. The main part of the book presents the analysis of the Russian/Soviet history of the social contract implementation at different stages under the contradictory development of the country, also explaining the forms of participation of the main social groups in the social contract. Finally, the author considers the essence, content, and evolution of the social contract ideas in the 20th - 21st century, their transformation and lessons of the social contract implementation at different stages of the contemporary society development.